Analysis of the Cultivation Area and Production Volume of Seaweed (Kappaphycus striatum) in Aimoli Village, West Alor District - Plaimo, Paulus Edison; Wabang, Imanuel Lamma (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2025)
The area of seaweed cultivation in the waters of Aimoli Village is not yet comprehensively known, and this condition affects information related to production volume. This study aims to uncover information related to the area of cultivation and production volume of seaweed (Kappaphycus striatum) in Aimoli Village, Northwest Alor District. If utilized optimally, it can support seaweed productivity in Aimoli Village. In this study, the methods used were weighing the seedlings, measuring the length of the ropes, counting the planting points on each rope, weighing the wet seaweed at harvest, and weighing the dry seaweed ready for sale with the same rope length as when weighed wet. Furthermore, to measure the area of cultivation, the classification of land area that has been utilized and not yet utilized was done using ArcGIS 10.8 software based on historical cultivation processes and visual observations. The results of the study in Aimoli Village indicate that seaweed production in 2024 will be as follows: Number of seaweed farmers: 35 people; Wet seaweed: 169 tons; Dry seaweed: 84 tons. For 2025, in the first cycle (January-March), wet seaweed production is 42 tons, while dry seaweed production is 31 tons. The total seaweed production for 2024-2025 is 115 tons. The area that can be used as seaweed cultivation land in Aimoli Village is 11.11 hectares, but it has only been utilized for seaweed cultivation development. Seaweed cultivation only covers an area of 2.22 hectares or 19.98%.